Handbook of research on global fashion management and merchandising - Vecchi, Alessandra; Buckley, Chitra 1959- (Advances in logistics, operations, and management science (ALOMS), 2016)
"This book explores the various facets of effective management procedures within the fashion industry, featuring research on entrepreneurship, operations management, marketing, business modeling, and fashion technology"...